Tathbiq Taqniyyah Fazzi Dalfi fi Siyaghah Ahdaf Ta’lim al-Mutalazimat al-‘Arabiyyah bi Istikhdam al-Ansyithah al-Tafa’uliyyah al-Iliktruniyyah - Nawi, Amani; Rahman, Asma Abdul (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This study aimed to collect experts’ opinions and consensus towards the objectives of teaching Arabic collocations. A questionnaire distributed to experts was the technique employed to garner the data. 12 professionals participated in this study, and Delphi's Method was used to analyse the data. In recent years, a great number of researchers have focused their emphases on the teaching of collocations to Arabic language learners. This is because multiple studies have shown that mastering collocational words affects one's proficiency in a second language. However, the precise use of Arabic collocation continues to be a substantial hurdle for students, to the point where it indirectly affects their competency to produce language. Additionally, educators lack direction and do not know where to begin. The study's findings demonstrated that all components of teaching objectives; knowledge, skill, and application met the fuzzy Delphi requirements, which called for a value threshold of less than 0.2 with a percentage of the experts’ group above 75%. This demonstrated that the fundamental components in determining the educational objectives contained critical components required by students according to experts’ agreements.